Cochlear Transcriptome Following Acoustic Trauma and Dexamethasone Administration Identified by a Combination of RNA-seq and DNA Microarray. Issue 7 (August 2017) - Maeda, Yukihide; Omichi, Ryotaro; Sugaya, Akiko; Kariya, Shin; Nishizaki, Kazunori
Abstract : Aim: To elucidate molecular mechanisms of noise-induced hearing loss (NIHL) and glucocorticoid therapy in the cochlea. Background: Glucocorticoids are used to treat many forms of acute sensorineural hearing loss, but their molecular action in the cochlea remains poorly understood. Methods: Dexamethasone was administered intraperitoneally immediately following acoustic overstimulation at 120 dB SPL for 2 hours to mice. The whole cochlear transcriptome was analyzed 12 and 24 hours following noise trauma and dexamethasone administration by both next-generation sequencing (RNA-seq) and DNA microarray. Differentially expressed genes (DEGs) with more than 2-fold changes after noise trauma and dexamethasone administration were identified. The functions of these DEGs were analyzed by David Bioinformatics Resources and a literature search. Results: Twelve hours after acoustic overstimulation, immune-related gene pathways such as "chemokine signaling activity, " "cytokine-cytokine receptor interaction, " and "cell adhesion molecules (CAMs) in the immune system" were significantly changed compared with the baseline level without noise. These DEGs were involved in immune and defense responses in the cochlea. Dexamethasone was administered to this NIHL model, and it modulated gene pathways of "cytokine-cytokine receptor interaction" and "cell adhesion molecules (CAMs) in the immune system" at 12 hours, compared with saline-injected control. Dexamethasone-dependent DEGs were also involved in immune and defense responses. A literature search showed that 10 other genes associated with hearing functions were regulated by dexamethasone both at 12 and 24 hours post-administration. Conclusion: Dexamethasone modulates the immune reaction in the traumatized cochlea following acoustic overstimulation. Dexamethasone may also regulate cochlear functions other than immunity. Abstract : Supplemental Digital Content is available in the text